Mazouco (Freixo de Espada-à-Cinta) : nótula arqueológica - Jorge, Vitor Oliveira; Jorge, Susana Oliveira; Sanches, Maria de Jesus; Ribeiro, João Pedro (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
.